PONDOK PESANTREN DAN ISSU JIHAD (Studi Pada Pondok Pesantren Karya Pembangunan Manado - Sirajuddin Ismail (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Manado, North Sulawesi. The focusresearch is Pesantren Karya Pembangunan. This research aims to findrelation between Pesantren and jihad issue. This use qualitative method.Data was collected by using interview and analyzed by qualitativedescription.This research indicates that students of this Pesantren equalize understandingof hardness in the form ofradicalism, fundamentalism, terrorism,war, demonstration; and differentiate with understanding of jihadbecause jihad in Islam has certain regulation that goals to obtain thekindness to human being.